2019
DOI: 10.21273/hortsci13572-18
|View full text |Cite
|
Sign up to set email alerts
|

Soil Amendments and Soil Profiling Impact on Macadamia Growth and Yield Performance

Abstract: Macadamia (Macadamia integrifolia, Maiden & Betche) orchard management in Hawaii can result in the loss of organic matter and soil degradation. The objective of this study was to determine the effects of macadamia husk mulch, husk mulch combined with biochar, husk mulch combined with effective microorganisms (EM), soil profiling, and wood chip mulch on yield, nut quality, root growth, and SPAD values during a 1-year study of mature macadamia orchards at two locations in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Higher water availability in the mulching treatment plots may be the result of the improved SPAD value working in conjunction with mulch application. Due to a change in leaf water concentration and its impact on SPAD, time of day is another potential source of variance in the samples (Galanti, et al, 2019). A close relationship between leaf chlorophyll content and photosynthetic rate was observed by Watanabe and Yoshida (1970) and stated that higher chlorophyll content is one of the important factors responsible for higher photosynthetic rate.…”
Section: Photosynthesis Rate (Pn) Stomatal Conductance (Gs) Intercell...mentioning
confidence: 96%
“…Higher water availability in the mulching treatment plots may be the result of the improved SPAD value working in conjunction with mulch application. Due to a change in leaf water concentration and its impact on SPAD, time of day is another potential source of variance in the samples (Galanti, et al, 2019). A close relationship between leaf chlorophyll content and photosynthetic rate was observed by Watanabe and Yoshida (1970) and stated that higher chlorophyll content is one of the important factors responsible for higher photosynthetic rate.…”
Section: Photosynthesis Rate (Pn) Stomatal Conductance (Gs) Intercell...mentioning
confidence: 96%
“…When the soil data were combined, papaya biomass was larger than the control, only in the surface-applied amendment. This was unexpected given that several studies using surface application of biochar with organic matter in perennial subtropical crops reported no or negative effects (Bass et al 2016;Galanti et al 2019). The yield response to surface application of biochar alone has also shown to be negligible (Sarauer et al 2018;Schnell et al 2012), though there are fewer studies examining this application method.…”
Section: Surface Vs Incorporated Amendment Applicationmentioning
confidence: 99%
“…The option for these crops is limited to surface application, which relies on movement of soluble nutrients with rainfall/irrigation, then biological bioturbation and vertical transport of solutes/particles over time (Major et al 2010). Application of biochar and compost to the soil surface of a banana plantation (Bass et al 2016) and a macadamia orchard (Galanti et al 2019) showed little difference in yield after 12 and 7 months, respectively, suggesting surface application may not be effective in this time frame, or that the amendments did not address a constraint of those soils.…”
Section: Introductionmentioning
confidence: 99%